2017
DOI: 10.1093/trstmh/trx015
|View full text |Cite
|
Sign up to set email alerts
|

Latent TB infection and pulmonary TB disease among patients with diabetes mellitus in Bandung, Indonesia

Abstract: LTBI prevalence in patients with DM was lower than in household contacts, but patients with DM were more likely to have TB disease. Further studies should explore possible benefits of LTBI screening and preventive therapy in patients with DM in TB-endemic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…In India, a population-based study conducted in six large cities from different regions estimated an age-standardized prevalence of type 2 diabetes among TB patients to be 39.1%. [21], [22], [23] Similarly, cross-sectional studies from have estimated DM prevalence among TB patients to be 15.6%, 18.27% and 38.6%, respectively with a prevalence of 15.8% in rural areas of Puducherry [24], [25], [26], [27]. In the current study, the prevalence of DM in TB patients was found to be 37.2%.…”
Section: Discussionsupporting
confidence: 56%
“…In India, a population-based study conducted in six large cities from different regions estimated an age-standardized prevalence of type 2 diabetes among TB patients to be 39.1%. [21], [22], [23] Similarly, cross-sectional studies from have estimated DM prevalence among TB patients to be 15.6%, 18.27% and 38.6%, respectively with a prevalence of 15.8% in rural areas of Puducherry [24], [25], [26], [27]. In the current study, the prevalence of DM in TB patients was found to be 37.2%.…”
Section: Discussionsupporting
confidence: 56%
“…M . tuberculosis pathogenesis and outcome of TB infection are impacted by several factors such as bacterial lineage [ 2 ], drug susceptibility of the strains [ 3 ], co-infection with HIV [ 4 ] or Cytomegalovirus (CMV) [ 5 ], comorbidities like diabetes [ 6 ], genetic predisposing factors (for instance IFN-γ/IL-12 deficiency [ 7 ]) and malnutrition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence supported an increased risk of developing TB disease for those with DM 5,8,10,4250 . However, this evidence did not differentiate the precise biological mechanism of whether DM is associated with increased proportion of TB infections entering the LFI state, as opposed to the LSI state ( Effect 2-Fast progression) ; increased susceptibility to develop TB disease among those with LSI ( Effect 3-Reactivation ); and/or increased susceptibility to TB reinfection among those with LSI ( Effect 4-Primary reinfection ).…”
Section: Resultsmentioning
confidence: 99%